2022
DOI: 10.3390/ijms232315273
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A Double-Edged Sword in Male Reproduction

Abstract: Autophagy, an evolutionarily conserved cell reprogramming mechanism, exists in all eukaryotic organisms. It is a fundamental and vital degradation/recycling pathway that removes undesirable components, such as cytoplasmic organelles, misfolded proteins, viruses, and intracellular bacteria, to provide energy and essential materials for organisms. The success of male reproduction depends on healthy testes, which are mainly composed of seminiferous tubules and mesenchyme. Seminiferous tubules are composed of Sert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 171 publications
0
2
0
Order By: Relevance
“…Contrary to the results presented in this study, Wei and colleagues observed that busulfan suppresses autophagy by halting the breakdown of autophagosomes, leading to the impairment of spermatogonial cells [ 39 ]. However, this finding does not contradict this study, as the effect of autophagy on male fertility is twofold [ 40 ]. Optimal autophagy can shield cells effectively from unfavorable environmental conditions, such as hypoxia, a lack of nutrients, oxidative stress, or the buildup of misfolded proteins.…”
Section: Discussioncontrasting
confidence: 52%
“…Contrary to the results presented in this study, Wei and colleagues observed that busulfan suppresses autophagy by halting the breakdown of autophagosomes, leading to the impairment of spermatogonial cells [ 39 ]. However, this finding does not contradict this study, as the effect of autophagy on male fertility is twofold [ 40 ]. Optimal autophagy can shield cells effectively from unfavorable environmental conditions, such as hypoxia, a lack of nutrients, oxidative stress, or the buildup of misfolded proteins.…”
Section: Discussioncontrasting
confidence: 52%
“…Cellular autophagy is often characterized as a 'double-edged sword' in various diseases and biological processes. It serves a protective role when functioning within normal limits but can become detrimental when overactivated (84,85). The alteration of gut microbiota interacts with cellular autophagy, contributing to disease development.…”
Section: The Influence Of Gut Microbiota On Other Cell Functions (Aut...mentioning
confidence: 99%
“…Understanding the particular autophagic responses to various stressors in the male reproductive system sheds light on prospective therapeutic techniques for reducing the negative effects of environmental insults on fertility. The male reproductive system, which includes the testes and epididymis, is a dynamic environment in which autophagy helps to regulate cellular remodeling and energy balance [3,52,53]. Autophagy in the testes helps to remove damaged or extra organelles, allowing for the creation of high-quality sperm.…”
Section: Autophagy Agonists and Antagonists Exacerbate Cellular Defectsmentioning
confidence: 99%
“…Autophagy, a conserved catabolic mechanism necessary for the maintenance of cellular equilibrium, has emerged as an important factor in a variety of physiological and pathological conditions [1,2]. While autophagy has been extensively investigated in the context of cellular maintenance and stress response, it has recently received a lot of attention for its role in the male reproductive system [3,4]. Understanding the complex connection between autophagy and male reproductive systems holds the prospect of yielding new insights into fertility, sperm production, and testicular health.…”
Section: Introductionmentioning
confidence: 99%